Plasma biomarkers for amyloid, tau, and cytokines in Down syndrome and sporadic Alzheimer’s disease - Startin, Carla M.; Ashton, Nicholas J.; Hamburg, Sarah; Hithersay, Rosalyn; Wiseman, Frances K.; Mok, Kin Y.; Hardy, John; Lleó, Alberto; Lovestone, Simon; Parnetti, Lucilla; Zetterberg, Henrik; Hye, Abdul; et al. (Alzheimer's research & therapy, 2019)
Down syndrome (DS), caused by chromosome 21 trisomy, is associated with an ultra-high risk of dementia due to Alzheimer's disease (AD), driven by amyloid precursor protein (APP) gene triplication. Understanding relevant molecular differences between those with DS, those with sporadic AD (sAD) without DS, and controls will aid in understanding AD development in DS. We explored group differences in plasma concentrations of amyloid-β peptides and tau (as their accumulation is a characteristic feature of AD) and cytokines (as the inflammatory response has been implicated in AD development, and immune dysfunction is common in DS). We used ultrasensitive assays to compare plasma concentrations of the amyloid-β peptides Aβ and Aβ , total tau (t-tau), and the cytokines IL1β, IL10, IL6, and TNFα between adults with DS (n = 31), adults with sAD (n = 27), and controls age-matched to the group with DS (n = 27), and explored relationships between molecular concentrations and with age within each group. In the group with DS, we also explored relationships with neurofilament light (NfL) concentration, due to its potential use as a biomarker for AD in DS. Aβ , Aβ , and IL1β concentrations were higher in DS, with a higher Aβ /Aβ ratio in controls. The group with DS showed moderate positive associations between concentrations of t-tau and both Aβ and IL1β. Only NfL concentration in the group with DS showed a significant positive association with age. Concentrations of Aβ and Aβ were much higher in adults with DS than in other groups, reflecting APP gene triplication, while no difference in the Aβ /Aβ ratio between those with DS and sAD may indicate similar processing and deposition of Aβ and Aβ in these groups. Higher concentrations of IL1β in DS may reflect an increased vulnerability to infections and/or an increased prevalence of autoimmune disorders, while the positive association between IL1β and t-tau in DS may indicate IL1β is associated with neurodegeneration. Finally, NfL concentration may be the most suitable biomarker for dementia progression in DS. The identification of such a biomarker is important to improve the detection of dementia and monitor its progression, and for designing clinical intervention studies.